2022
DOI: 10.15388/amed.2021.29.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Jackstone: A Calculus “Toy” in the Bladder. A Case Report of Rare Entity and Comprehensive Review of the Literature

Abstract: Background: An uncommon type of urinary calculus, Jackstone was named after its distinct resemblance to the children’s game “Jacks.” It typically involves the bladder and, to a lesser extent, the upper urinary tract.Case Presentation: Herein, we report a case of Jackstone vesical calculus in a 75-year-old male undergoing elective open prostate surgery for benign prostate hyperplasia refractory to medical treatment. Preoperative clinical examination revealed intermittent gross hematuria and symptoms suggestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Therefore, medical imaging examinations and visual inspection are necessary for diagnosis. Patients with jackstones often exhibit intermittent gross hematuria, obstructive lower urinary tract symptoms, and abdominal or flank pain, making these patients seek medical attention[ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, medical imaging examinations and visual inspection are necessary for diagnosis. Patients with jackstones often exhibit intermittent gross hematuria, obstructive lower urinary tract symptoms, and abdominal or flank pain, making these patients seek medical attention[ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, jackstones were usually located in the renal pelvis[ 8 , 9 ]. Symeonidis et al [ 3 ] summarized 14 previously published cases of jackstones found in the urinary tract: 78.6% of patients had single jackstones; 2 cases had renal stones and the remaining 12 patients had bladder stones[ 3 ]. However, the exact pathophysiology of jackstone development remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] The global prevalence of urolithiasis and the existence of rare forms/types of urolithiasis in other parts of the urinary tract, in addition to the typical renal or ureteral occurrence, must not be forgotten. [ 11 ] We believe that this case report will guide the management of giant prostatic urethral stones.…”
Section: Introductionmentioning
confidence: 95%
“…The article entitled: Jackstone: A Calculus "Toy" in the Bladder. A Case Report of Rare Entity and Comprehensive Review of the Literature [1], is as far as we know the first medical review concerning Jackstone (JS) in the literature.…”
mentioning
confidence: 99%